A STUDY OF PACKAGE INSERTS: HOW ACCURATE IS THE INFORMATION PROVIDED? - KRISHNABEN N PATEL; PRASHANT SHAH; PRATIT VYAS (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to critically analyze the accuracy of the drug package inserts. An accurate package insert that is patient-friendly, written in a regional language, and based on guidelines can benefit patients, prescribers, and health-care providers, improving overall healthcare in our society. Methods: The study was a cross-sectional observational type of study. One hundred and fifty package inserts were collected from the pharmacy store of a tertiary care teaching hospital in Gujarat. Package inserts with the same drug formulation and from the same company were excluded from the study. The collected package insert data were analyzed for accuracy and compliance concerning guidelines based on the “Drug and Cosmetics Act (1940) and Rules (1945).” Results: A total of 150 drug package inserts, among them 89 were injectable, 53 were oral, and 8 were topical preparations. In therapeutic indication, posology and method of administration were present in 150 (100%) package inserts. Contra-indications, interaction with other medicaments and other forms of interaction, undesirable effects/side effects, and antidote for overdosing parameters were present, respectively, in 145 (96.66%), 133 (86.66%), 148 (98.66%), and 127 (84.66%) package inserts. In pharmaceutical information; list of excipients, shelf life in the medical product as packaged for sale, special precautions for storage, and instructions for use/handling were present, respectively, in 26 (17.33%), 81 (54%), 145 (96.66%), and 82 (54.66%). Conclusion: We found that all package inserts included in our study were not accurate as per the Central Drugs Standard Control Organization guideline. If accurate information in the package insert is available, it can be beneficial for the patient’s healthcare.